Usual and Unusual Musculoskeletal Sequalae of COVID 19! - Bagaria, Vaibhav (Indian J Orthop, 2021)
Today the orthopedic world with respect to COVID remains focused on resumption of elective surgery and impact of the pandemic on scientific activities. However, it is equally important that we keep our eyes on the phenomenon that is quietly unraveling in front of the eyes. The phenomenon of post-COVID musculoskeletal sequelae may become a major orthopedic public health problem in coming months and needs to be investigated in depth. The usual post-COVID symptoms include arthralgia and myalgia that are common in many viral diseases. It is the unusual symptoms like occurrence of primary septic joint infection and elevated rates of post-operative infections that warrant attention and further investigation. Could this be attributed to immune consumption leading to a phase of temporary immunosuppression is a matter of speculation and hypothesizing. A short communication here reveals a glimpse of musculoskeletal sequalae that COVID may bring in coming months. These could be usual arthralgia or myalgia which are self-limiting but could also be more sinister like spontaneous osteonecrosis and primary joint infections.